PENGEMBANGAN BLENDED LEARNING UNTUK CALON GURU PAUD PADA MATA KULIAH PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS - Siron, Yubaedi (UNIVERSITAS SLAMET RIYADI, 2024)
The Early Childhood Education (PIAUD) department in UIN Jakarta still needs toimprove higher quality lecture programs following the present technology. Thisstudy aims to develop blended learning in the Special Needs Education (SNE) courseat the PIAUD department in UIN Jakarta. This study uses a research and developmentmethod using the Dick and Carey model with 10 stages. The sample in thisstudy was 55 PIAUD students taking SNE courses. Data were collected using observationand tests. Quantitative data were tested using the t-test to measure the pre andpost-test values. The results showed the development of blended learning carried outin the SNE course in the PIAUD study program can be developed adequately with amedia expert score of 3.38 with a good category, a material expert of 3.5 with a goodcategory, and a learning design expert of 3.44 with a good category. The effectivenessof the implementation of blended learning in the SNE course in the PIAUDdepartment was 34.5, from an average pretest score of 43.47 to an average post-testscore of 77.97